The Role of Teachers in Counselling and Human Relations in the Canadian Setting - McNeilly, Russell A.; McCann, William E. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this paper is to show that the teacher has an important part to play in the development of counselling in the schools.Many a counsellor has failed as a result of his inability to involve teachers in the process of developing human relations since he does not know how to involve teachers and significant others in this process. The paper emphasizes a model known as the integrative approach showing the characteristics that are necessary for sound relationships. Definite ways for implementing this model are presented, and it is emphasized that the counsellor should be the agent for developing this approach. The counsellor ought to educate the teacher in the understanding of the functions for developing positive human relations, not in the sense of adding to workloads, but as part of the process of learning and teaching.